Residential area deprivation predicts smoking habit independently of individual educational level and occupational social class. A cross sectional study in the Norfolk cohort of the European Investigation into Cancer (EPIC-Norfolk). Issue 4 (1st April 2003) - Shohaimi, S; Luben, R; Wareham, N; Day, N; Bingham, S; Welch, A; Oakes, S; Khaw, K-T
Abstract : Objectives: To investigate the independent association between individual and area based measures of socioeconomic status and cigarette smoking habit. Design and setting: Cross sectional, population based study. Participants and methods: 12 579 men and 15 132 women aged 39–79 years living in the general community participating in the EPIC-Norfolk Study in 1993–1997. The association between social class, educational status, Townsend residential deprivation level, and cigarette smoking status was examined. Main outcome measures: Cigarette smoking status at baseline survey. Results: Social class, educational level, and residential deprivation level independently related to cigarette smoking habit in both men and women. Multivariate age adjusted odds ratios for current smoking in men were 1.62 (95% CI 1.45 to 1.81) for manual compared with non-manual social class, 1.32 (95% CI 1.17 to 1.48) for those with educational level less than O level compared with those with O level qualifications or higher and 1.84 (95% CI 1.62 to 2.08) for high versus low area deprivation level. For women, the odds ratios for current smoking for manual social class were 1.14 (95% CI 1.03 to 1.27); 1.31 (95% CI 1.18 to 1.46) for low educational level and 1.68 (95% CI 1.49 to 1.90) for high residential deprivation respectively. Conclusions: Residential deprivation level using the Townsend score, individual social class, and educational level all independently predict smoking habit in both men and women. Efforts to reduce cigarette smoking need to tackle not just individual but also area based factors. Understanding the specific factors in deprived areas that influence smoking habit may help inform preventive efforts.